Changes in Breeding Strategy for Needs in a Liberalized Cotton Industry in Uganda - Serunjogi, L.K.; Mukasa, S.B.; Odeke, W.; Ochola, G. (SAARI, 2000)
Commercial cotton (G. hirsutum L.) production has been based on BPA and SATU varieties, grown in two ecological zones. Both have had a strong world market, the stronger, longer and finer fiber BPA finding a different market niche. The collapse of the seed replacement system developed by the Department of Agriculture and liberalization of the cotton industry has resulted in problems of variety deterioration and mixing, leading to non-uniform and poor quality lint. These new challenges necessitated changes in breeding objectives and strategy. In 1993 breeding work was revived at SAARI with the strategy of developing a variety with good adaptation in the two zones for high yield, resistance to pests and high lint quality. Selections were made from existing and purified BPA and SATU stocks, and progenies arising from intraand inter-variety crosses. Variety checks and advanced lines of 9 SATU and 11 BPA stocks were compared, using single and combined analysis of variance over 8 locations and 3 years ordination and cluster analyses. At a three-group level, one group membership was consistent over the three seasons. The members expressed similar response patterns and good yield and constituted the elite entries. G x E interactions were not significant for yield but fiber characteristics of BPA entries were influenced by the environments. SATU and BPA lines performance was comparable except at locations of very low environmental index where SATU was better. Pattern analysis results indicate that the higher quality BPA which is also more bacterial blight resistant, can be grown in a wider range of environments than previously anticipated.
Keywords: Changes; Breeding Strategy; Liberalized Cotton Industry